Factores condicionantes y su influencia en el cumplimiento del esquema de vacunación en lactantes de 6-24 meses atendidos en el Centro de Salud “El Mamey”, Babahoyo – Los Ríos diciembre 2022 - mayo 2023. - Ayala Álava, Joel Josué (2023)
Immunization is the process by which a person becomes immune to an infectious disease through the administration of a vaccine. Vaccines stimulate the body's own immune system to protect the person against subsequent infections or diseases. For this reason, it is of utmost importance to know the conditioning factors and their influence on compliance with the vaccination schedule in infants aged 6-24 months, given that, according to reports from the World Health Organization, there is a decrease in immunization coverage. The COVID-19 pandemic and associated interruptions have put health systems under pressure: 23 million children were not vaccinated in 2020, which is 3.7 million more than in 2019 and the highest number since 2009 (WHO, 2022). Therefore the preservation of immunization is the basis for maintaining health, its sustainable use contributes to the safety and reduction of preventable pathologies. This systematic literature review and field study, with its methodology of a mixed qualitative-quantitative approach, will allow objective data to be collected and analyzed from their perspectives and interpretation. The conditioning factors that affect non-compliance with the vaccination schedule are shown, where it has been possible to contemplate that 40% of the respondents stated that they did not comply with the vaccination schedule due to lack of time, in addition to 30% due to illness and 68% due to fear of Covid 19.